Adjustment trade and growth in developed and developing countries - Blackhurst, Richard; Marian, Nicolas; Tumlir, Jan. (Geneva : GATT, 1978)
This empirical essay hammered on trade liberation, protection and interdependence' with emphasis to associated problems in area of adjustment and trade, providing, where possible.
Bibliography: p. 95-98.
asm; 23/04/19
Loans
Keywords: Tariff; Developing countries; Commerce; Developing countries